Bulletin of FVR sermons volume 2 : empowering the people - Ramos, Fidel V., 1928- ([Manila, Philippines] : Ramos Peace and Development Foundation, 2008)
"Sermonizing" can be viewed by many as arrogantly and even unrealistically pontificating from on high.
Chapter I : Marching with our partners -- Chapter II : Learning from our history of overcoming challenges -- Chapter III : Fighting poverty through people empowerment -- Chapter IV : Work in progress : strengthening our democracy -- Chapter V : Giving peace a chance
Includes index.
Keywords: RAMOS, FIDEL VALDEZ, -- 1928- POLITICAL AND SOCIAL VIEWS